Criminal Law and Scope of Criminal Law - Yolla Veronica Sembiring; Yasmirah Mandasari Saragih; Sumarno Sumarno; Juita Novalia Br. Barus; Welli Nirpa Pasaribu (International Journal of Law and Society, 2024)
Unitary state The Republic of Indonesia is a country with foundations on law ( Rechts Staat ). In space its scope there is a number of one of the principles that is principle legality . Scope​ law criminal interests oriented​ general . Criminal law is knowledge basics that everyone should know and understand student law . Based on description above​ as for formulation problem in This research is What do you mean with law criminal and how room scope law criminal . As for goals study based on formulation the problem above is For know and analyze understanding law criminal and for know and analyze room scope law criminal . This research is of a nature descriptive , analytical and comparative , viz research that describes , describes and analyzes data as well compare data regarding law criminal and space its scope . In principle there are two different meanings on Criminal Law , the so -called with ius poenale and ius puniendi . Space principles scope enactment rule law the punishment is divided become four that is principle Territoriality ( territorialiteits beginningsel ), basic Nationality active , basic Protection (National Passive ), and principles universality ( universaliteits beginssel ).